Widespread Metastatic Gastric Signet-Ring Cell Carcinoma Shown by 68Ga-FAPI PET/CT. (February 2021) - Fan, Chunlei; Guo, Wei; Su, Guoqiang; Chen, Bo; Chen, Haojun
Abstract : Abstract: The present study compared 68 Ga-FAPI and 18 F-FDG PET/CT in a patient with GSRCC (gastric signet-ring cell carcinoma). In this case, 68 Ga-FAPI PET/CT shows much higher tumor-to-background contrast of primary tumor and reveals more metastatic lesions than 18 F-FDG PET/CT. This case demonstrates that 68 Ga-FAPI PET/CT outperforms 18 F-FDG in identifying both primary and metastatic lesions in GSRCC.